Ethnic diversity and economic instability in Africa : interdisciplinary perspectives - Hino, Hiroyuki, 1945- (Cambridge University Press, 2012)
There is growing consensus in the development economics literature that ethnic diversity is a very significant factor in explaining Africa's poor economic performance. Ethnic Diversity and Economic Instability in Africa challenges this conventional wisdom. Drawing on the insights of historians, anthropologists and political scientists as well as development economists, this book questions whether ethnicity is the most useful organising principle by which to examine the economic development of Africa, arguing that it is a more fluid and contingent concept than economic models allow. Instead, the authors explore the actual experience of ethnicity in Africa and propose new methods of measuring ethnic diversity and inequalities. Finally some tentative conclusions are reached regarding appropriate policy reforms.